Islamofascism: Four Avenues to the Use of an Epithet. - Schulze, Reinhard (Welt des Islams, 2012)
In this paper I want to reconstruct the genealogy of relating Islam to fascism and fascism to Islam by assembling evidence from Western discourses. Such a reconstruction of course suffers from the fact that it has to draw a picture based solely on a collection of idiographic interpretations. The result is more a mosaic than a coherent narrative. My purpose is not to discuss again the meaning of the current ideological discourse on Islamofascism and the use of Fascism as an epithet for Islamism or even for Islam. Nor do I want to examine the fallibility of identifying certain Islamic political traditions as "fascist" or to explore the historical interaction between Islamic political discourses and Fascism from the 1920s to the 1940s. My intention is to study the mechanism and meaning of relating Fascism to Islam and Islam to Fascism. Starting with a look at the semantic expressing this relation, I will continue by examining the scope of the current usage in the Western public. Next I will investigate the general application of Islam as an epithet for secular political traditions and cultures since the early 19 century. Finally, I will concentrate on the use of Islam as an epithet for Fascism and Nazism in the 1930s and 1940s. I will conclude with some observations on current practice, which fuses and equates the epithetical use of Islam and Fascism. My main thesis is that Islam has been instrumental in splitting off ideological and cultural traditions considered adversarial from one's own social, political, or cultural context. The current usage of Islamofascism reverses this mechanism, as now fascism has become instrumental in splitting off Islam from the Western context.